2023
DOI: 10.1002/ohn.405
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Total Thyroidectomy for Amiodarone‐Induced Thyrotoxicosis According to Left Ventricular Ejection Fraction

Abstract: ObjectiveTo report cardiac outcomes after total thyroidectomy for amiodarone‐induced thyrotoxicosis according to the baseline left ventricular ejection fraction in a tertiary referral center.Study DesignRetrospective, monocentric.SettingThe tertiary health care system.MethodsPatients who underwent total thyroidectomy for amiodarone‐induced thyrotoxicosis between 2010 and 2020 with age >18 and available preoperative left ventricular ejection fraction were included in this study. Patients were dichotomized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…The favorable result obtained when surgery was performed in this high-risk setting was ascribed to its capability to promptly restore euthyroidism with a consequent improvement in systolic function (mean LVEF 45% pre-surgery vs 50% post-surgery, p < 0.0001) [ 17 ]. This has been confirmed by other studies, particularly in patients with severe systolic dysfunction [ 54 , 56 ].…”
Section: Novel Concepts Emerging In Ait Therapysupporting
confidence: 86%
See 3 more Smart Citations
“…The favorable result obtained when surgery was performed in this high-risk setting was ascribed to its capability to promptly restore euthyroidism with a consequent improvement in systolic function (mean LVEF 45% pre-surgery vs 50% post-surgery, p < 0.0001) [ 17 ]. This has been confirmed by other studies, particularly in patients with severe systolic dysfunction [ 54 , 56 ].…”
Section: Novel Concepts Emerging In Ait Therapysupporting
confidence: 86%
“…At multivariate analysis, duration of exposure to thyroid hormone excess was confirmed as a significant risk factor for mortality (HR 1.004, IQR 1.000–1.006) [ 57 ], as previously postulated by other authors [ 58 ]. The same results were recently confirmed in another study from a different country which reported a baseline LVEF < 40% and a longer time period prior to surgery as the main determinants of cardiac mortality [ 54 ].…”
Section: Novel Concepts Emerging In Ait Therapysupporting
confidence: 66%
See 2 more Smart Citations